Ответ:
[tex]4\frac{5}{9}-2\frac{2}{3}=4-2+ \frac{5}{9}-\frac{6}{9}=2-\frac{1}{9}=1\frac{8}{9}[/tex]
Пошаговое объяснение:
[tex]4 \frac{5}{9} - 2 \frac{2}{3} = \frac{41}{9} - \frac{8}{3} = \frac{17}{9} = 1 \ \frac{8}{9} [/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex]4\frac{5}{9}-2\frac{2}{3}=4-2+ \frac{5}{9}-\frac{6}{9}=2-\frac{1}{9}=1\frac{8}{9}[/tex]
Пошаговое объяснение:
Ответ:
[tex]4 \frac{5}{9} - 2 \frac{2}{3} = \frac{41}{9} - \frac{8}{3} = \frac{17}{9} = 1 \ \frac{8}{9} [/tex]